Local Fractional Variational Iteration Method for Local Fractional Poisson Equations in Two Independent Variables - Chen, Li (2014)
The local fractional Poisson equations in two independent variables that appear in mathematical physics involving the local fractional derivatives are investigated in this paper. The approximate solutions with the nondifferentiable functions are obtained by using the local fractional variational iteration method.